1988
DOI: 10.1002/ps.2780240202
|View full text |Cite
|
Sign up to set email alerts
|

Minimum concentration levels of methyl bromide required for full efficacy against seven species of stored‐product beetle at two temperatures

Abstract: The dosages of methyl bromide required to control insect pests can be expressed as concentration, time (Ct) products for concentrations down to a certain minimal level, here defined as the efficacy threshold, below which Habers Ct rule (C×t=k,a constant for mortality) no longer applies. Twelve strains of seven species of stored‐product beetle were tested to identify efficacy threshold concentrations at 15°C and 25°C. For each strain the efficacy threshold was higher at 25°C than at 15°C. Different species diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Fumigants are generally less effective at lower temperatures, and this must be taken into account in the development of an effective fumigation protocol 1. For example, stored‐product insects have been found to be more tolerant to phosphine at 15 °C,26 and methyl bromide was found to be more effective against stored‐grain beetles at temperatures above 15 °C 27. The present fumigation results with ethyl formate/CO 2 conducted at 25 and 15 °C over 24 h show that the high level of efficacy is maintained at the lower temperature, although further research investigating efficacy over a wider range of grain temperatures is warranted from these initial comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Fumigants are generally less effective at lower temperatures, and this must be taken into account in the development of an effective fumigation protocol 1. For example, stored‐product insects have been found to be more tolerant to phosphine at 15 °C,26 and methyl bromide was found to be more effective against stored‐grain beetles at temperatures above 15 °C 27. The present fumigation results with ethyl formate/CO 2 conducted at 25 and 15 °C over 24 h show that the high level of efficacy is maintained at the lower temperature, although further research investigating efficacy over a wider range of grain temperatures is warranted from these initial comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The CUE process has enabled the continued use of methyl bromide in ßour mills to allow additional time to Þnd technically and economically viable alternatives. Methyl bromide in laboratory studies is highly effective, because it rapidly kills all stages of many pest species (Bell 1988). However, published data on its Þeld efÞcacy is limited (Campbell and Arbogast 2004, Toews et al 2006, Small 2007.…”
mentioning
confidence: 99%
“…Unlike the case with protectants, which require the commodity to be moved to apply the insecticide, a fumigant gas can be applied in situ , reaching all parts of the storage and stored commodity (W eller and M orton , 2001). Its toxicity to insects and practical applications are well documented (L indgren et al., 1958; B ond et al., 1969; W ainman et al., 1975; B ell , 1988; R ajendran and M uralidharan , 2001). It has been observed that fumigants at the recommended doses do not impair the germination of wheat (L indgren et al., 1958).…”
Section: Introductionmentioning
confidence: 99%